(3cTa GdeYGfi aj TQM MQR GdCeGfi (B((3GdTGWHjI (B)s - (3jhSa Hf CHi HcQ GdNdGWi GdeYQha HGHf NWjH HjJ GdCHGQs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3hPdc jOd Ydi fSjGf GdBNQI hPdc ZGjI GdLgd hGdWjT hbdI GdJCed ddYhGbH ajLQ Edi GdehL ajLQ Edi GdgdGc s
(3BNQgG (B:s
(3agPG CUGHJge faMGJge hHQcGJgG QVhGf , Ydjge CLejYf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs